The difference in potential harms between whole blood and component blood transfusion in major bleeding: A rapid systematic review and meta-analysis of RCTs - Geneen, LJ; Brunskill, SJ; Doree, C; Estcourt, LJ; Green, L (Elsevier, 2021)
Our aim was to assess whether there is a difference in outcomes of potential “all-cause” harm in the transfusion of whole blood (WB) compared to blood components (BC) for any bleeding patient regardless of age or clinical condition. We searched multiple electronic databases using a pre-defined search strategy from inception to 2nd March 2021. 1 reviewer screened, extracted, and analysed data, with verification by a second reviewer of all decisions. We used Cochrane ROB1 and GRADE to assess the quality of the evidence. We used predefined subgroups of trauma and non-trauma studies in the analysis. We included six RCTs (618 participants) which compared WB and BC transfusion therapy in major bleeding, one trauma trial (n = 107), and 5 surgical trials (non-trauma) (n = 511). We GRADED evidence as very-low for all outcomes (downgraded for high and unclear risk of bias, small sample size, and wide confidence intervals around the estimate). Our primary outcome (all-cause mortality at 24-hours and 30-days) was reported in 3 out of 6 included trials. There was no evidence of a difference in mortality of WB compared to BC therapy (very-low certainty evidence). There may be a benefit of WB therapy compared to BC therapy in the non-trauma subgroup, with a reduction in the duration of oxygen dependence (1 study; n = 60; mean difference 5.9 fewer hours [95% Confidence Interval [CI] -10.83, –0.99] in WB group), and a reduction in hospital stay (1 study, n = 64, median difference 6 fewer days in WB group) (very-low certainty evidence). For the remaining outcomes (organ injury, mechanical ventilation and intensive care unit requirement, infection, arterial/venous thrombotic events, and haemolytic transfusion reaction) there was no difference between WB and BC therapy (wide CI, crossing line of no effect), though many of these outcomes were based on small single studies (very-low certainty evidence). In conclusion, there appears to be little to no difference in harms between WB and BC therapy, based on small studies with very low certainty of the evidence. Further large trials are required to establish the overall safety of WB compared to BC, and to assess differences between trauma and non-trauma patients.